Determinants of Integrity of Financial Reports in State-Owned Companies - Yulisa, Erli; Khairudin, Khairudin (LPPPIPublishing, 2025)
Financial reports must have high integrity, which means they must be based on honest and impartial moral principles. This study aims to test and analyze the effect of auditor independence, financial distress, institutional ownership and independent commissioners on the integrity of financial reports in state-owned companies listed on the IDX in 2021-2023. The final sample of this study was 34 samples. The test was carried out using multiple linear regression analysis, where the integrity of financial reports was measured using accounting conservatism. The results of this study are that auditor independence, institutional ownership and independent commissioners have an influence positive and significant impact on the integrity of financial reports . Financial distress has an influence negative and significant impact on the integrity of financial reports.